Mekanisme Pengeluaran Dana Warehouse Pada PT Tri Jaya Teknik Karawang - Muhammad Yusril Pahmi; Syifa Pramudita Faddila (Madani: Jurnal Ilmiah Multidisiplin, 2023)
PT Tri Jaya Teknik Karawang is an engineering company engaged in fabrication, machining and stamping parts. PT Tri Jaya Teknik Karawang produces Stamping Parts, Fabrication Tanks, Ducting, Conveyors and Machining. With services that are supported by the strategic geographical location of the workshop and an adequate workshop area. The implementation of the company's activities raised in this practical work article is the Mechanism of Spending Warehouse Funds which aims to find out how the spending of warehouse funds with the constraints found in data input when we place orders with vendors is not the same as the actual arrival of goods. The research method used by the author is a qualitative method. In this case the observation of each company's activities is used as a research to solve existing problems, such as constraints on the use of warehouse funds with one solution which is ordering goods from vendors by proposing the company to place orders in a larger quantity so that they can maintain stability in demand. expected in the future, and can reduce the risk of shortage of goods.